1987
DOI: 10.1073/pnas.84.2.561
|View full text |Cite
|
Sign up to set email alerts
|

Left globus pallidus abnormality in never-medicated patients with schizophrenia.

Abstract: Schizophrenia is a severe psychiatric disorder characterized by onset in young adulthood, the occurrence of hallucinations and delusions, and the development of enduring psychosocial disability. The pathophysiology of this disorder remains unknown. Studies of cerebral blood flow and metabolism designed to identify brain abnormalities in schizophrenia have been limited by inadequate methods of anatomical localization and the possibility of persistent medication effects. We have now used positron emission tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(88 citation statements)
references
References 33 publications
7
79
1
1
Order By: Relevance
“…That we observed changes that were larger on the right than on the left side of the basal ganglia in males (Cohen et al 1997) is consistent with a previous all-male PET study of neuroleptics (Buchsbaum et al 1992b). In contrast to the right-sided basal ganglia asymmetry in neuroleptictreated patients, our own study (Cohen et al 1998) and two other studies of either all-male or predominantly all-male patients (Buchsbaum et al 1987;Early et al 1987), not receiving neuroleptic medication, have suggested a left greater than right asymmetry in metabolic rates in the putamen. The basis of the underlying asymmetries in blood flow and metabolic rates in the basal ganglia of males may rest with asymmetries in the dopamine system.…”
Section: Possible Causes Of the Sex-specific Response To Neurolepticscontrasting
confidence: 76%
See 1 more Smart Citation
“…That we observed changes that were larger on the right than on the left side of the basal ganglia in males (Cohen et al 1997) is consistent with a previous all-male PET study of neuroleptics (Buchsbaum et al 1992b). In contrast to the right-sided basal ganglia asymmetry in neuroleptictreated patients, our own study (Cohen et al 1998) and two other studies of either all-male or predominantly all-male patients (Buchsbaum et al 1987;Early et al 1987), not receiving neuroleptic medication, have suggested a left greater than right asymmetry in metabolic rates in the putamen. The basis of the underlying asymmetries in blood flow and metabolic rates in the basal ganglia of males may rest with asymmetries in the dopamine system.…”
Section: Possible Causes Of the Sex-specific Response To Neurolepticscontrasting
confidence: 76%
“…In women, but not in men, clozapine is equally as effective in increasing basal ganglia metabolism as fluphenazine, and both clozapine and fluphenazine decrease cingulate metabolism. Because it is unlikely that the schizophrenic patients we have studied while performing CPT have abnormally low basal ganglia or abnormally elevated cingulate metabolism before treatment (see discussion in Cohen et al 1997 andCohen et al 1998;Kotrla and Weinberger 1995;Tamminga et al 1992;Early et al 1987), these sex differences would seem to strengthen the compensation hypothesis.…”
Section: Discussionmentioning
confidence: 88%
“…To our knowledge, this is the first application of the ASL method to investigate differences in resting perfusion in a schizotypy group. Given that the study groups only differed on the presence of schizotypal traits, and that hippocampal hyperperfusion has been reported in patients with psychosis (Friston et al, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014, 2015; although see Andreasen et al, 1997; Catafau et al, 1994; Early et al, 1987; Parellada et al, 1994), and in people at CHR of sychosis (Allen et al, 2017, 2016; Schobel et al, 2013), our study findings suggest that increased hippocampal activity (reflected in an elevation of regional perfusion) is also involved in the expression of subclinical psychotic‐like experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the hippocampus, other brain regions of significantly elevated resting perfusion in schizophrenia patients compared with healthy controls have involved the basal ganglia and middle temporal lobes (Pinkham et al, 2011), cerebellum, brainstem, and thalamus (Scheef et al, 2010). Noteworthy, while not directly focusing on the hippocampus as a specific region, initial PET and SPECT studies did not find increased perfusion in medial temporal regions (Andreasen et al, 1997; Catafau et al, 1994; Early, Reiman, Raichle, & Spitznagel, 1987; Parellada et al, 1994). A possible source for the inconsistencies noted among individual studies is that resting perfusion research in patients with schizophrenia is complicated by antipsychotic exposure (Lahti et al, 2006; Lahti, Weiler, Holcomb, Tamminga, & Cropsey, 2009; Medoff, Holcomb, Lahti, & Tamminga, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex was examined based on our earlier findings (Cohen et al 1987) that the metabolic rates of prefrontal cortex regions of interest, but not regions of interest in the pre-motor or orbital frontal cortex were reduced in the schizophrenic patients. When the prefrontal cortex is referred to in the text in the comparison between groups, it is the mean of the left and right anterior and posterior ROIs of the frontal cortex in Planes B, C, and D. The basal ganglia was also examined for differences because of the reports of both abnormally high and abnormally low metabolic rates in schizophrenia (Buchsbaum et al 1992a;Early et al 1987;Resnick et al 1988;Wolkin et al 1985). When the multivariate analyses were significant, student t -tests were performed to localize the findings.…”
Section: Discussionmentioning
confidence: 99%